2007
DOI: 10.1051/0004-6361:20067011
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric analysis of Ellerman bombs in the Ca II, H$\mathsf{\alpha}$, and UV range

Abstract: Context. Even if Ellerman bombs have been observed in the Hα line within emerging magnetic flux regions since the early 20th century, their origin and the mechanisms that lead to their formation have been strongly debated. Recently, new arguments in favor of chromospheric magnetic reconnection have been advanced. Ellerman bombs seem to be the signature of reconnections that take place during the emergence of the magnetic field. Aims. We have observed an active region presenting emergence of magnetic flux. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
87
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 31 publications
(55 reference statements)
12
87
1
2
Order By: Relevance
“…An interesting result of the work by Pariat et al (2007) was that the undulatory magnetic flux system seemed to be connected to the photosphere by bald patches (BPs). BPs are associated with fieldlines having dips tangent to the photosphere and, thus, it is likely to be related with the U segments of the undulating field.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting result of the work by Pariat et al (2007) was that the undulatory magnetic flux system seemed to be connected to the photosphere by bald patches (BPs). BPs are associated with fieldlines having dips tangent to the photosphere and, thus, it is likely to be related with the U segments of the undulating field.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors found them to be co-spatial with facular features and network bright points (Bruzek 1972;Kitai & Muller 1984;Stellmacher & Wiehr 1991), others argued that not every brightening in the wing of Hα line is a signature of EBs (Watanabe et al 2011;Rutten et al 2013). For instance, the EBs shown by Roy & Leparskas (1973) match fairly well with the ones shown by Pariat et al (2007). However, it is not clear if these objects are indeed the same features reported by Ellerman (1917) or Socas-Navarro et al (2006).…”
Section: Introductionmentioning
confidence: 98%
“…Ellerman bombs have a typical lifetime of a few minutes, but can live up to an hour (Kurokawa et al 1982;Georgoulis et al 2002;Pariat et al 2007;Bello González et al 2013). The brightening peaks at about Hα ± 1.2 Å and fades away toward ±5 Å (Berlicki et al 2010;Kneer 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But velocity fields and magnetic fields observed at high levels strongly depend on photospheric values, so spectropolarimetry of different wavelength ranges are often required. Time scales smaller than one minute characterize local events such as the triggering of waves across sunspots (Tziotziou et al 2007) or emerging fluxes and Ellerman bombs in active regions (Pariat et al 2007). But short time scales not only concern small-size events.…”
Section: Introductionmentioning
confidence: 99%